Body Composition and Cognitive Functioning in a Sample of Active Elders - Crespillo-Jurado, Miriam; Delgado-Giralt, Joaquín; Reigal, Rafael Enrique; Rosado, Antonio; Wallace-Ruiz, Agustín; Juárez-Ruiz de Mier, Rocío; Morales-Sánchez, Verónica; Morillo-Baro, Juan Pablo; Hernández-Mendo, Antonio (Frontiers in Psychology, 2019)
The purpose of this paper was to analyze the relationship between body composition and cognitive functioning in a sample of older people. A total of 106 older adults between the ages of 60 and 79 were involved in physical activity (M = 67.57; SD = 4.96). 31.10% were men (n = 33) and 68.90% were women (n = 73). The instruments used to assess cognitive capacity were the Trail Making Test (forms A and B), the Stroop Test and the Attention Test d2. The body composition of the participants was evaluated by electrical bioimpedance. Correlation analyses, linear regression (successive steps) and cluster analysis were carried out to analyse the relationships between the different measures. The results obtained indicated the existence of significant relationships between the analyzed variables, and the predictive capacity of the percentage of muscle mass over the evaluated cognitive functioning variables was highlighted. These results suggest that healthy lifestyles, including physical activity, are essential for well-being and quality of life in older people. In addition, it appears from the results found that it would be necessary for these lifestyles to contribute to preserving their level of physical condition, because of the possible impact it would have on their health.